Defaunation disrupts the behavior of large terrestrial vertebrates, impacting ecological functions in the Amazon - da Silva Batista, Gabriela; Brocardo, Carlos R.; Castro, Arlison B.; Fogliatti, Emiliano F.; Galetti, Mauro [UNESP]; Pires, Mathias M.; Fadini, Rodrigo F. (Elsevier, 2025)
Wildlife defaunation in tropical forests disrupts critical ecological functions such as predation, seed dispersal, and nutrient cycling. While exclusion experiments are commonly used to investigate the effects of wildlife loss on plant diversity and vegetation structure, their potential impact on broader ecosystem functions remains underexplored. Here we investigate how defaunation could affect ecosystem functions in the Amazon rainforest by quantifying the changes in the occurrence and frequency of behaviors exhibited by terrestrial mammals induced by experimental defaunation. Using camera traps, we recorded vertebrate behaviors across exclusion and control plots, categorizing them into feeding, excretion/defecation, bioturbation, and trampling. We then calculated weighted standardized indices, integrating behavior frequency and body mass, to assess the potential local impacts of vertebrates across plots. We found that all behaviors were drastically reduced (>95 % reduction) under severe defaunation conditions, primarily due to the absence of medium- and large-bodied mammals and birds. In defaunated plots, small mammals partially performed some behaviors, but they were unable to compensate for the loss of larger species. These results highlight the substantial reduction in critical vertebrate behaviors and suggest that such changes can significantly disrupt ecosystem functions in defaunated tropical forests.
Keywords: Camera traps; Ecosystem services; Ethogram; Exclusion experiment; Tropical forest; Vertebrates; Vertebrates.